2020
DOI: 10.1093/hsw/hlaa009
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Cystic Fibrosis for Mental Health Care Coordinators and Providers: Collaborating to Promote Wellness

Abstract: To maximize health, individuals with cystic fibrosis (CF) follow a complex, burdensome daily care regimen. Managing CF is associated with a range of significant biopsychosocial challenges and places individuals with CF, and their caregivers, at greater risk for developing anxiety and depression. To promote wellness and address the potential barriers that affect management of this complex chronic illness, many individuals would benefit from treatment from a behavioral health provider. Social workers within mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Participants were recruited from a pool of 124 awCF at Amsterdam UMC between March-October, 2021. All awCF with mild or moderate PHQ-9/GAD-7 scores (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), without either score above moderate (≥15), were eligible and were invited to participate (N = 12). Two eligible candidates declined participation; One due to a mild language barrier and extended stay outside the Netherlands, and another due to time limitations and the fact that this person was already receiving psychological treatment.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were recruited from a pool of 124 awCF at Amsterdam UMC between March-October, 2021. All awCF with mild or moderate PHQ-9/GAD-7 scores (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), without either score above moderate (≥15), were eligible and were invited to participate (N = 12). Two eligible candidates declined participation; One due to a mild language barrier and extended stay outside the Netherlands, and another due to time limitations and the fact that this person was already receiving psychological treatment.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Consequently, CF Foundation (CFF) and European CF Society (ECFS) guidelines recommend routine screening, treatment, and preventative efforts for depression and anxiety 1–3 . However, many barriers to accessing mental health care for awCF remain 4,5 . These may include financial and insurance limitations, long waitlists, and balancing mental health care needs with high CF treatment burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite increased attention to mental health in CF, barriers remain, such as stigma, insurance/financial limitations, long waitlists, lack of understanding of CF by community-based providers, and a dearth of providers trained in evidence-based interventions such as CBT. 5,6 The COVID-19 pandemic has exposed and worsened the shortage of available mental health providers. 7 CF exacerbations can disrupt continuity of mental health care, particularly for those with advanced disease who may require additional support.…”
Section: Introductionmentioning
confidence: 99%
“…Screening provides a tremendous opportunity for early intervention to prevent negative outcomes. However, access to evidence-based mental health care that addresses the needs of pwCF is limited; barriers to access include insurance or financial obstacles, the lack of understanding about CF by community-based providers, limited availability of mental health care providers with training in evidence-based interventions, and long waitlists for care (Mueller et al, 2020). A survey of 1,454 CF healthcare professionals conducted by the CFF and ECFS concluded that CF centers need additional training and educational resources to implement the mental health guidelines.…”
Section: Introductionmentioning
confidence: 99%